Animal-derived proteins as stabilizers of Pickering emulsions: applications and challenges - Souza, Ana Carla Aguiar de; Briceno, Julio Cesar Colivet; Pires de Amorin Trindade, Dennia; Conceição, Edemilson Cardoso da; Oliveira, Tatianne Ferreira de; Gómez-Estaca, Joaquín; Silva, Flavio (Food Science and Technology, 2025)
Emulsions are precursors for formulating stable food products with high demand worldwide and efficient cosmetics that can provide the capability of delivering bioavailable active ingredients. The development of Pickering emulsions is crucial because they can eliminate the more prolonged need for chemical stabilizers, increasing the sustainability and stability of the formulation. Conventional emulsion formulations employ chemical surfactants to stabilize. Nevertheless, incorporating proteins as emulsion stabilizers improves stability and attractiveness. Therefore, a systematic reference review is essential to give theoretical knowledge of Pickering emulsions and their structures and properties to review critical aspects, the mechanisms, and the vital applications to promote their stability. The subject of this review article is research focused on developing new protein modification technologies, improving their properties, and extending their applications. The applications of casein, whey protein, and egg albumin as emulsion stabilizers primarily focus on widely published literature. The present study focuses on evaluating the food industrial applications of casein, whey protein, egg albumin, lactoferrin, and myofibrils. The bioavailability of casein, whey protein, and egg albumin is essential for applying in Pickering emulsion, and it can be a limiting factor. We are opening new opportunities and options for utilizing alternative proteins, such as emulsion stabilizers.